A Comparative Study of Balloon Blowing and Pursed-Lips Breathing Exercises on Oxygen Saturation Levels Among COPD Patients in The High Care Unit of Bali Mandara General Hospital - Setiawan, I Made Gunadi; Martini, Ni Made Dwi Ayu; Wijaya, I Putu Artha; Suardani, Ni Nyoman (Jurnal Kesehatan, 2026)
Introduction: COPD is a respiratory disease that causes chronic airflow disruption and progressive airway obstruction, as a result of many factors. The management of COPD therapy is carried out with pharmacological and non-pharmacological therapies. Various non-pharmacological techniques can be performed, including Balloon Blowing and Pursed Lips Breathing (PLB). Method: This study uses a quasi experimental research method (Quasi Experimental Design) with the research design used is Nonequivalent Control Group Design. Where the experimental group and the control group were not randomly selected. The results of the comparative test analysis of balloon blowing and pursed lips breathing exercises on the oxygen saturation of COPD patients in the HCU Room of Bali Mandara Hospital using the results of the Repeated ANOVA test Results: The results of the comparative test analysis of balloon blowing and pursed lips breathing exercises on the oxygen saturation of COPD patients in the HCU Room of Bali Mandara Hospital using the results of the Repeated ANOVA test obtained a p-value of 1,000 in the saturation before the intervention and a p-value of 0.304 in the column after the intervention, with a p value of > 0.05, showing that there was no difference between balloon blowing and pursed lips breathing exercises on the oxygen saturation level in COPD patients because Both interventions have an effect on increasing oxygen saturation in COPD patients in the HCU Room of Bali Mandara Hospital Conclusion: The results of this study are in line with a study that compared pursed lips breathing (PLB) and balloon blowing exercises to increase oxygen saturation in COPD patients, the results of which were no difference between PLB exercises and balloon blowing on oxygen saturation in COPD patients. There was an increase in clinical oxygen saturation due to the median value before the intervention: 94, however, there was no statistically significant improvement in the two interventions.